Impact of melphalan day -1 vs day -2 on outcomes after autologous stem cell transplant for multiple myeloma - Merino, Aimee; Shanley, Ryan; Rashid, Faridullah; Langer, Jenna; Dolan, Michelle; Tu, Sarah; Jurdi, Najla El; Rogosheske, John; Hanna, Kirollos; DeFor, Todd; Janakiram, Murali; Weisdorf, Daniel (Frontiers in Immunology, 2024)
Background: Melphalan is the most common conditioning regimen used prior to autologous stem cell transplant (ASCT), however there are varying data on optimal melphalan timing prior to transplant for best safety and efficacy. Historically, ASCT conditioning consisted of melphalan 200 mg/m 2 on Day-2 (D-2) (48 hours prior to ASCT), but many institutions have since adopted a melphalan protocol with administration on Day-1 (D-1) (24 hours prior to SCT) or split dosing over the 2 days. The optimal timing of melphalan has yet to be determined.In this single center retrospective study we analyzed transplant outcomes for patients between March 2011 to September 2020 admitted for high dose, single agent melphalan 200 mg/m 2 on D-1 vs. D-2. The primary outcomes were time to neutrophil and platelet engraftment.Secondary outcomes include incidence of hospital readmission within 30 days, two-year progression free survival, and two-year overall survival.Results: 366 patients were studied (D-2 n = 269 and D-1 n = 97). The incidence of high-risk cytogenetics was similar between the two groups (37% vs 40%). Median days to absolute neutrophil count engraftment was similar at 11 days in the D-2 and D-1 cohort (n = 269, range [0][1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Median days to platelet engraftment >20,000/mcL was 18 days for D-2 melphalan (range: 0-28, IQR 17-20) versus 19 days for D-1 melphalan (range:0-32, IQR 17-21). Overall survival at 2 years post-transplant was similar in both cohorts (94%; p=0.76) and PFS was 70% in the D-2 compared to 78% in D-1 (p=0.15). In a multivariable model including age and performance status, hospital re-admission within 30 days of transplant was higher in the D-1 cohort (odds ratio 1.9; p=0.01).This study demonstrates similar neutrophil and platelet engraftment in D-1 and D-2 melphalan cohorts with similar 2-year PFS and OS. Either D-2 or D-1 melphalan dosing schedule is safe and effective.